An investigation of the social, emotional, and character development practices and perceptions of Kansas school-based agricultural education teachers - James, KaCee (My University, 2025)
For decades, schools have addressed students’ basic needs from dental to eye exams in addition to teaching them academic content. Given the increasing concern for student mental health, many states have recently begun requiring educators to incorporate social and emotional learning into the educational setting. In 2012, the Kansas State Department of Education adopted a framework to promote social, emotional, and character development (SECD) competencies. The Kansas SECD standards provide a framework for schools to incorporate social and emotional learning (SEL) alongside character development, supporting students in their personal, social, and character growth. These standards include practicing citizenship, personal safety, problem-solving, risk prevention, and promoting a positive school culture. This study investigated the perceptions and practices of Kansas school-based agricultural education (SBAE) teachers regarding social, emotional, and character development. SBAE teachers are uniquely positioned to foster these skills through the major areas of agricultural education that encompass the three-component model – classroom instruction, student organization, and work-based learning. The Kansas SECD standards and the Collaborative for Academic, Social, and Emotional Learning guided this research. The central question was, “How do Kansas SBAE teachers perceive they foster social, emotional, and character development in their programs?’ A collective case study was conducted to examine the perceptions and teaching strategies of six Kansas SBAE teachers to understand how they incorporate social, emotional, and character skills in their programs. The teacher participants were interviewed via Zoom using a semi-structured interview protocol. After the interviews, additional supporting documents, including pictures of learning spaces, lesson plans, and sample classroom rules and expectations, were gathered from the teacher participants. The supporting documents provided triangulation and added to the credibility of the findings. The data collected through the case study was used to explain how teachers integrate social, emotional, and character learning in their classrooms and FFA chapters. This study identified key themes related to Kansas SBAE teachers’ perceptions and practices concerning SECD. Teachers saw themselves as both educators and mentors, roles reflected in recurring themes: SECD as a foundation, relationships and safe environments, and challenges of formal SECD. Additionally, four themes emerged in relation to how teachers implement SECD in their classrooms: creating a supportive and relational learning environment, intentionally integrating SECD through agricultural education, empowering students through responsibility, and modeling desired behaviors and attitudes for student development. The findings from this study contribute to the growing body of knowledge on SECD within SBAE and can inform teachers, teacher educators, and professional development efforts. Additional research is needed to measure the impact of SBAE teachers’ SECD practices on student outcomes. Teacher preparation programs should explicitly incorporate strategies to develop pre-service teachers’ confidence and fluency in SECD, including examining ways to model positive behaviors, build strong relationships, and create supportive learning environments.
Keywords: School-based agricultural education; Social and emotional learning; Mental health; Teaching practices; FFA